Ein Zweifelsfall: zweifeln im Deutschen - Fischer, Markus (ZAS Papers in Linguistics, 2003)
Two main types of sentences are traditionally distinguished in the context of semantic theories of questions and answers: declarative sentences, corresponding to statements, and interrogative sentences, corresponding to questions. The interrogative forms can be further subdivided into dialectical ones (yes-no-questions) and non-dialectical ones (constituent questions). These distinctions are made for both root and embedded sentences. The predicates that select sentential complements fall into three classes: predicates that license only declaratives, those that allow only for interrogatives, and those that embed both types of sentences. In this connection, verbs of doubt are interesting in that they allow for declaratives as well as dialectical interrogatives, while non-dialectical interrogatives do not seem to be appropriate complements.In what follows, our main concern will be with the German verb of doubt zweifeln and its possible sentential complements. Speaker intuitions as to which constructions are grammatical or acceptable vary, particularily with respect to rare expressions like zweifeln. Therefore, interviews and corpus analysis were applied as a means to acquire reliable linguistic data. These as well as data from historical sources and from some languages other than German (esp. English and Italian) are presented and analysed. In the last section, based on the notion of ‘subjective probability’, an attempt is made at explaining the observations.